Manual of obstetrics - Evans, Arthur T.; DeFranco, Emily (Wolters Kluwer, 2021)
"Manual of Obstetrics skillfully addresses the care, assessment, and complications, as well as other emerging issues handled daily by obstetric providers. Top-rated among obstetrics manuals, this practical, authoritative text is both an excellent desk reference and on-the-spot guide. Essential data and commentary are provided on all the major areas of obstetric care, obstetric complications, maternal complications, fetal assessment, fetal complications, fetal therapy, fetal intervention issues, endocrine disorders, and neonatal care"--